Effects of Sevoflurane and Propofol on Posttraumatic Stress Disorder After Emergency Trauma: A Double-Blind Randomized Controlled Trial - Zhong, Junfeng; Li, Yan; Fang, Lichao; Han, Dan; Gong, Chuhao; Hu, Shuangyan; Wang, Rongguo; Wang, Liwei; Yao, Rui; Li, Beiping; Zhu, Yangzi; Yu, Youjia (Frontiers in Psychiatry, 2022)
Objective Posttraumatic stress disorder (PTSD) is a frequent and disabling consequence of traumatic events. A previous study found that early use of propofol was a potential risk factor for PTSD. This prospective study aimed to investigate the effect of propofol and sevoflurane on PTSD after emergency surgery in trauma patients. Methods A total of 300 trauma patients undergoing emergency surgery were randomly divided into two groups and anesthetized with propofol and/or sevoflurane. Perioperative clinical data were collected. The incidence of PTSD was evaluated with the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5) in the two groups 1 month after the operation. The relevance of the injury time and CAPS-5 scores was assessed by Spearman correlation analysis. Logistic regression analysis was used to analyze the risk factors for PTSD. Results The incidence of PTSD in the propofol group was higher than that in the sevoflurane group 1 month postoperatively (23.2 vs. 12.2%, P = 0.014). The injury time was negatively correlated with the CAPS-5 score in the propofol group (r = -0.226, P < 0.001). In the logistic regression analysis, the utilization of propofol was an independent risk factor for PTSD (P = 0.017). Conclusion Early use of propofol general anesthesia in emergency surgery for trauma patients may increase the risk of PTSD. Clinical Trial Registration www.chictr.org.cn, identifier: ChiCTR2100050202.